Characteristic of Soil Moisture in Indonesia Using ESA CCI Satellites Products - Fatkhuroyan Fatkhuroyan; Trinah Wati; Roni Kurniawan (Faculty of Geography, Universitas Gadjah Mada, 2021)
Soil moisture (SM) is one of the energy and water exchange main drivers between the atmosphere and land surface. The study aims to analyze the soil moisture characteristics in Indonesia on monthly and seasonal time scales. The analysis uses mapping of monthly and seasonal ESA CCI SM satellite products of mean daily from 1979 to 2016. The results showed the spatial and temporal variability of SM in Indonesia. Sumatera has SM values > 0.3 m3/m3 almost throughout the year. Besides, Java has SM values > 0.3 m3/m3 from January to April and October to December while 0.2-0.3 m3/m3 from May to September. In Borneo, the SM value > 0.3 m3/m3 from February to June and November to December, while from July to September are 0.2-0.3 m3/m3. Sulawesi has SM values > 0.3 m3/m3 from January to July, on December, and 0.2-0.3 m3/m3 from august to November. Bali to Nusa Tenggara have SM values between 0.2-0.3 m3/m3 throughout the year, except <0.2 m3/m3 in Sumba, Timor Island, and Central Lombok from June to November. Maluku has SM values between 0.2-0.3 m3/m3 throughout the year, while Papua has SM values >0.3 m3/m3 throughout the year, except in Jayawijaya Mountain and South Papua. The ESA CCI SM product is essential for monitoring SM in Indonesia.